Penggunaan Pasir Proppant Sebagai Media Hydraulic Fracturing Menggunakan Standar Api - Rp 19C - Dahrul Effendi; Angga Naufal Firdaus (Institut Teknologi Sains Bandung, 2023)
To reduce the gap between national production capacity and oil consumption, which is likely to become wider in the future, it is necessary to seek out petroleum resources, including from shallow depth oil sands. Shallow depth oil sand exploitation technology is very different from conventional petroleum exploitation technology, while tight reservoirs are unconventional natural reservoirs trapped in tight sandstone but have the potential to be developed with fracture patterns, requiring hydraulic fracture stimulation. In hydraulic fracturing activities it is necessary to use proppant. Proppant itself is used to stimulate hydraulic fractures to function as a wedge so that the fractures that have formed do not close again. From the results of property tests using 3 sand samples, namely locations 1, 2, and 3, starting from roundness and sphericity tests, acid solubility, turbidity, bulk density, and impact resistance at location 1 were entered into the API. RP19C Specifications. After testing the proppant sand in the laboratory, the results of this research show that sample location 1 has the potential to be used as a proppant sand medium because by testing the sand properties of sample location 1 it still meets the API RP19C requirements with a roundness of 0.6 and a roundness of 0.7 while the minimum API specifications RP19C ≥ 0.6, location 1 acid solubility test results obtained 1.051% while API RP19C specifications ≤ 3%, location 1 turbidity test results obtained 205 NTU while API RP19C specifications ≤ 250 NTU, from location 1 bulk density testing results obtained 1,461 in the test The crush resistance of 20/40 mesh experienced damage of 55.11% - 61.05%, 40/70 mesh 14.81% -24.33%, for 70/140 mesh it was 10.61% - 46.71%. And during the crush resistance test, location 1 experienced a slight crush resistance test of the 20/40 mesh, which experienced damage of 55.11% - 61.05%